Parental perceptions of school-based influenza immunisation in Ontario, Canada: a qualitative study. Issue 6 (5th June 2014) - MacDougall, Donna; Crowe, Lois; Pereira, Jennifer A; Kwong, Jeffrey C; Quach, Susan; Wormsbecker, Anne E; Ramsay, Hilary; Salvadori, Marina I; Russell, Margaret L; ,
Abstract : Objective: To understand the perspectives of Ontario parents regarding the advantages and disadvantages of adding influenza immunisation to the currently existing Ontario school-based immunisation programmes. Design: Descriptive qualitative study. Participants: Parents of school-age children in Ontario, Canada, who were recruited using a variety of electronic strategies (social media, emails and media releases), and identified as eligible (Ontario resident, parent of one or more school-age children, able to read/write English) on the basis of a screening questionnaire. We used stratified purposeful sampling to obtain maximum variation in two groups: parents who had ever immunised at least one child against influenza or who had never done so. We conducted focus groups (teleconference or internet forum) and individual interviews to collect data. Thematic analysis was used to analyse the data. Setting: Ontario, Canada. Results: Of the 55 participants, 16 took part in four teleconference focus groups, 35 in 6 internet forum focus groups and four in individual interviews conducted between October 2012 and February 2013. Participants who stated that a school-based influenza immunisation programme would be worthwhile for their child valued its convenience and its potential to reduce influenza transmission without interfering with the family routine. However, most thought that for a programme to be acceptable, it would need to be well designed and voluntary, with adequate parental control and transparent communication between the key stakeholder groups of public health, schools and parents. Conclusions: These results will benefit decision-makers in the public health and education sectors as they consider the advantages and disadvantages of immunising children in schools as part of a system-wide influenza prevention approach. Further research is needed to assess the perceptions of school board and public health stakeholders.